Age-specific risk factors of depression among the oldest-old - evidence from the multicenter AgeCoDe-AgeQualiDe study - Luppa, Melanie; Pabst, Alexander; Löbner, Margrit; Mallon, Tina; Brettschneider, Christian; Hajek, André; Heser, Kathrin; Kleineidam, Luca; Weyerer, Siegfried; Werle, Jochen; Pentzek, Michael; Weeg, Dagmar; et al. (Frontiers in psychiatry, 2024)
Purpose: The present study aimed to investigate age-group-specific incidence rates and risk factors for depressive symptoms in the highest age groups. Methods: Data were derived from a prospective multicenter cohort study conducted in primary care - the AgeCoDe/AgeQualiDe study. In total, 2,436 patients 75 years and older were followed from baseline to ninth follow-up. To assess depressive symptoms, the short version of the Geriatric Depression Scale (GDS-15, cutoff score 6) was used. Age-specific competing risk regressions were performed to analyze risk factors for incident depressive symptoms in different age groups (75 to 79, 80 to 84, 85+ years), taking into account the accumulated mortality. Results: The age-specific incidence rate of depression was 33 (95% CI 29-38), 46 (95% CI 40-52) and 63 (95% CI 45-87) per 1,000 person years for the initial age groups 75 to 79, 80 to 84 and 85+ years, respectively. In competing risk regression models, female sex, mobility as well as vision impairment, and subjective cognitive decline (SCD) were found to be risk factors for incident depression for age group 75 to 79, female sex, single/separated marital status, mobility as well as hearing impairment, and SCD for age group 80 to 84, and mobility impairment for age group 85+. Conclusion: Depressive symptoms in latest life are common and the incidence increases with increasing age. Modifiable and differing risk factors across the highest age groups open up the possibility of specifically tailored prevention concepts.
Gesehen am 27.01.2025